Gaya Hidup Hedonis Ditinjau Dari Kecerdasan Finansial Mahasiswa Di Kota Madiun - Novita Erliana Sari, Dwi Nila Andriani (Universitas PGRI Madiun, 2019)
This study aims to determine the hedonic lifestyle of students in terms of financial intelligence. Hedonic lifestyles are the patterns of life of people who rely on pleasure. Financial intelligence is a person's ability to manage finances. It is assumed that student financial intelligence influences the hedonic style of students. This research is quantitative research. The research sample was all students in Madiun who were still actively studying. This study was tested with SPSS. 17 with simple linear regression analysis. The results of this study are hedonic lifestyles not influenced by financial literacy. Conclusions can be drawn from this study, although student financial intelligence can be said to be good, but with regard to lifestyle, students tend to choose what they enjoy for their lives.